The Effectiveness of the Secondary Weapon of the West Virginia State Police - Davis, Jesse Andrew (2003)
The present study examines the effectiveness of the West Virginia State Troopers’ secondary weapon, Oleoresin Capsicum (OC) pepper spray (CAP-STUN®), as a means of alternative use of force for non-cooperative subjects. The WV State Police have adopted OC in an effort to reduce the number and severity of injuries sustained by suspects. This method was adopted as an optional means to effect arrests through non-lethal force. The use of OC can control and restrain individuals while causing the least possible harm to the individuals without increasing danger to troopers or others. Questionnaires were sent to West Virginia State Troopers for their responses and opinions of the efficiency of OC pepper spray. The study explores troopers’ perceptions of OC as a weapon of safe and effective use-of-force